Research Center Personnel, Acknowledgments - L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2017)
Research Center Personnel, Southeast Agricultural Research Center, Kansas We thank the following individuals, organizations, and firms that contributed to this year’s research programs through financial support, product donations, or services.
Keywords: Personnel; Acknowledgments